红尘若梦 = Memoirs of a white snake. - Tan, Shirley. (2012)
‘Am I dreaming of the Butterfly, or am I in the Butterfly’s dream’. Memoirs of a White Snake narrates the meeting between a jaded deity and a young, vengeful demon. The latter learns a lesson about the meaning of life (or its transience) through the deity’s self-sacrifice. Given a chance of rebirth, the demon then goes on a journey. Each chapter tells a different story as we explore the world through the eyes of the demon.